Metronomic Chemotherapy in Triple-Negative Metastatic Breast Cancer: The Future Is Now?. (3rd December 2017) - Cazzaniga, M. E.; Cortesi, L.; Ferzi, A.; Scaltriti, L.; Cicchiello, F.; Ciccarese, M.; Torre, S. Della; Villa, F.; Giordano, M.; Verusio, C.; Nicolini, M.; Gambaro, A. R.; et al.
Abstract : Triple-negative breast cancer (TNBC) shows a very bad prognosis, even in early stages of disease. Metronomic chemotherapy refers to the minimum biologically effective dose of a chemotherapy agent given as a continuous dosing regimen with no prolonged drug-free breaks that leads to antitumor activity. In the present article, we review preclinical and clinical data of metronomic administration of chemotherapy agents with or without biological agents in TNBC cell lines and patients, contextually reporting data from the VICTOR-2 study in the subgroup of patients with TNBC, in order to stimulate new ideas for the design of clinical trials in this subset of patients.